ЙЎЛОВЧИЛАР ОҚИМИ МОНИТОРИНГИ - Йўлдошев, Д.Ф.; Эргашев, Б.З. (SCIENCE and SOCIETY, 2023)
Today providing a reliable transport service in city buses is associated with constant monitoring and regular analysis of public transport passenger traffic. The demand for direct buses is increasing in the city of Tashkent day by day. The scientific approach to this issue requires the analysis of passenger flow monitoring methods. The article examines the methods and criteria of passenger flow monitoring.
Keywords: passenger flow; monitoring; public transport; urban agglomeration; transport network